The economic costs of limited health literacy in China: evidence from China's National Health Literacy Surveillance data - Lefan Liu; Jing Huang; Guoxing Li; Zhuo Chen; Tianfeng He (BMC, 2022)
Abstract Background Limited health literacy is a public health challenge contributing to the rising health care costs. We assess the economic costs of limited health literacy in China using data from the National Health Literacy Surveillance survey. Methods Our data includes a sample of 6316 residents aged 15-69 years old living in Ningbo, China, in 2019. We use box plots to examine the distribution of out-of-pocket health expenditure by the level of health literacy. We then use the estimates from a two-part model to assess the contribution of limited health literacy to individual medical spending and the aggregate health expenditure at different levels of health literacy for the adult population in Ningbo. Results Medical costs of limited health literacy are about 10% (177 CNY or about 25 USD) of the annual medical expense of a resident aged 15-69 living in Ningbo. The medical cost of limited health literacy is greater among the rural, female, and older groups than others. If the proportion of people with adequate health literacy increases from 22 to 30% (the target level by 2030), the aggregate out-of-pocket health expenditure in Ningbo will decrease by 100 million CNY (14 million USD), or 0.88% of the 2019 Ningbo government expenditure on health care. Conclusions This paper highlights the direct and indirect economic costs associated with limited health literacy. The results should help policymakers evaluate the cost-effectiveness of relevant programs that aim to improve residents' health literacy.